Prevalence and Factors Associated with New Students Drinker in Bangkok Metropolitan High Schools - Chirapradispol, Rujapa; Pichayapinyo, Panan; Lagampan, Sunee; Sujirarat, Dusit (Journal of Public Health Nursing, 2018)
Alcohol consumption is one of the risk factors leading to premature death and inappropriate sexual behavior. Despite the national policy prohibiting the sale of alcohol to people aged less than 20 years old, the number of new drinkers is likely to continue to increase from 16% presently among Thai youth aged 15 – 19 years old. The sample population of this study consisted of 830 students randomly selected from 10-12th grade students in the Bangkok metropolitan area. Using the Theory of Planned Behavior, data were collected by self-administered questionnaires for Attitude, Subjective Norm, Perceived Behavior, and Intention. Statistical analysis was performed using descriptive statistics entered into the SPSS statistical program. Among this population, there were 246 new drinkers (29.6%) and they each drank approximately one drink per month. The majority of them were boys, and their grade point average (GPA) was at a moderate level. Factors significantly related to the onset of drinking were gender, education, grade point average, other drug use, living patterns, alcohol consumption behavior of family members, family income per month, Perceived Behavior and Intention (p < 0.05). Attitude and Subjective Norm were not significant, but when performing further analysis for subjective norm, friends were found to influence students to become new drinkers. It is recommended that schools organize sessions to inform student attitudes about the Perceived Behavior of alcohol consumption. Student participation in peer group activities could also serve to lessen willingness to exhibit alcohol drinking behaviors. Parents and family members should also provide examples for their children and should consider the negative consequences of drinking alcohol in the family as priority.